Pengaruh Omzet Usaha dan Nilai Jaminan Terhadap Kelancaran Pengembalian Pembiayaan Murabahah pada UMKM di BMT (The Effect of Turnover and Collateral Value on The Smooth Repayment of Murabahah Financing for MSME Customers) - Azizah, Nur; Kaban, Reny Fitriana; Hadiyati, Puji (Perisai : Islamic Banking and Finance Journal, 2020)
This study aims to determine the effect of turnover and collateral value on the smooth repayment of murabahah financing for MSME customers at BMT At-Taqwa Kemanggisan. This study uses quantitative methods with primary obtained data by interviews with BMT and secondary obtained data from annual report of BMT debtors. The research method used purposive sampling with sample of 286 debtors and the data is processed by STATA application version 14.2. The results show that the variables of turnover and collateral value simultaneously effect the smooth repayment of murabahah financing with a significance value of 0.0000. Meanwhile with the partial test only the turnover variable has effect on the smooth repayment of murabaha financing with significance value 0.023.